It all comes back to you - Wiesner, Melissa (Forever, 2025)
"An unforgettable and heart-wrenching romance about a woman haunted by her past and the man who could never let her go. Anna works two jobs to get herself through college and never, ever talks about her family. It's easier to keep her distance from everyone until she can finally leave her old life behind. That is, until chance throws her together with Gabe... Gabe is top of the class, in an exclusive fraternity, and has a big, perfect, warm-hearted family. He is everything Anna is not, but their connection is undeniable. His silver-blue eyes pierce right through her, and he makes her laugh in ways she never thought possible. But Anna would do anything to stop Gabe from discovering her darkest secret and the real reason she goes home every night to a cold, silent apartment. When Gabe and his family get close to the truth, Anna runs, vowing to never see them again. But forever is a long time... Years later, tragedy brings Anna back to the town she grew up in-a place she escaped a decade ago. When Gabe wraps his strong arms around her, it's like finally finding home. But when the truth comes out after all these years, will both their worlds come crashing down? Gabe is the one person Anna trusts most, but what if he has secrets, too? And how much pain can two hearts endure, before they are torn apart forever?"--